2021
DOI: 10.1002/ecy.3598
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bee emergence along an elevation gradient: Implications for climate change revealed by a transplant experiment

Abstract: Bees experience differences in thermal tolerance based on their geographical range; however, there are virtually no studies that examine how overwintering temperatures may influence immature survival rates. Here, we conducted a transplant experiment along an elevation gradient to test for climate-change effects on immature overwinter survival using movement along elevational gradient for a community of 26 cavity-nesting bee species in the family Megachilidae along the San Francisco Peaks, Arizona elevational g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 90 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Further, pollinators in montane environments may be especially susceptible to changing climate; competition between pollinators may become more prevalent with increased elevation if the range expansion of lower elevation pollinators encroaches on the space typically reserved for the higher-elevation pollinator groups, such as bumblebees, non-syrphid flies, or cold-adapted butterflies [4,81]. These higher-elevation insect pollinators often have narrow niches restricted to upper altitudes with cooler temperatures and low seasonal temperature variation [81][82][83]. Unfortunately, areas supporting these conditions are expected to shrink disproportionately under future climate scenarios [84], potentially causing certain pollinator taxa to reduce their ranges to remain within optimal habitat [81,85].…”
Section: Discussionmentioning
confidence: 99%
“…Further, pollinators in montane environments may be especially susceptible to changing climate; competition between pollinators may become more prevalent with increased elevation if the range expansion of lower elevation pollinators encroaches on the space typically reserved for the higher-elevation pollinator groups, such as bumblebees, non-syrphid flies, or cold-adapted butterflies [4,81]. These higher-elevation insect pollinators often have narrow niches restricted to upper altitudes with cooler temperatures and low seasonal temperature variation [81][82][83]. Unfortunately, areas supporting these conditions are expected to shrink disproportionately under future climate scenarios [84], potentially causing certain pollinator taxa to reduce their ranges to remain within optimal habitat [81,85].…”
Section: Discussionmentioning
confidence: 99%
“…Megachilidae is a cosmopolitan solitary bee family, having over 4100 species worldwide 19 ; the genus Megachile , which comprises leafcutters, has about half of these species and is globally distributed 19 . A recent study suggests that they can even be found at higher altitudes above 2500 m asl 20 . Many leafcutter bee species are critical pollinators of several commercial crops, such as alfalfa 21 .…”
Section: Introductionmentioning
confidence: 97%
“…By surveying rose plants of several sites of seven latitudinal points in south India (8°N to 12°N) and northeast India (26°N to 27°N), two altitudinal ranges (at sea level to over 2000 m asl) along the Western Ghats and the central Himalayas biodiversity hotspots, and two landscape types (urban and rural), the study examined the pattern and the drivers of rose plant use by leafcutter bees. Based on the literature evidence 15 , 18 , 20 , we expected that leafcutter bees use roses in all landscapes and altitudes. By comparing the brood success of brood sheathed by the rose leaves and non-rose leaves, we tested the hypothesis that rose leaves do not hamper brood development.…”
Section: Introductionmentioning
confidence: 99%
“…As heterothermic ectotherms they rely on environmental conditions to maintain non-lethal body temperatures (Wieser 1973, Huey & Stevenson 1979). This is compounded by a reliance on resources (e.g., nesting resources, plants) that are often disturbed by human activity (Grab et al 2019, McCabe et al 2021). Documented changes in bee populations over time can help determine how human activity may impact bees with different life history characteristics, with knock-on effects for their ecological relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Bees with narrow phenological windows and bees that are dietary specialists are likely to be more susceptible to declines, given their reliance on a smaller pool of available resources (Bartomeus et al 2013). Solitary and desert-adapted bees are expected to be particularly vulnerable to climate change (Sala et al 2000, Loarie et al 2009, Vale & Brito 2015, Hamblin et al 2017, Burdine & McCluney 2019, McCabe et al 2021, but see Silva et al 2018), given the thermal and hygric stressors already evident in their environment. To date, no studies have tracked changes in morphology of any solitary bees in desert ecosystems.…”
Section: Introductionmentioning
confidence: 99%